2021
DOI: 10.1093/nar/gkab662
|View full text |Cite
|
Sign up to set email alerts
|

Antisense ribosomal siRNAs inhibit RNA polymerase I-directed transcription in C. elegans

Abstract: Eukaryotic cells express a wide variety of endogenous small regulatory RNAs that function in the nucleus. We previously found that erroneous rRNAs induce the generation of antisense ribosomal siRNAs (risiRNAs) which silence the expression of rRNAs via the nuclear RNAi defective (Nrde) pathway. To further understand the biological roles and mechanisms of this class of small regulatory RNAs, we conducted forward genetic screening to identify factors involved in risiRNA generation in Caenorhabditis elegans. We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 54 publications
0
42
0
Order By: Relevance
“…This response requires the nuclear Argonaute HRDE-1 and may reflect stalling of RNA polymerase II and/or pre-mRNA processing, causing nascent transcripts to accumulate at the locus. Stalling of RNA polymerase has previously been implicated in nuclear RNAi 36,37 and several lines of evidence have linked RNAi and splicing, including apparent co-evolution of the RNAi and splicing machineries 38 , splicing factors identified as HRDE-1 interactors 39,40 , sRNA defects associated with mutations or knock down of spliceosome components 41,42 and insensitivity to nuclear RNAi of an endogenous transcript whose introns were removed by genome editing 43 .…”
Section: Pathway Ii: Hrde-1 Reduces But Does Not Eliminate Transcriptionmentioning
confidence: 99%
“…This response requires the nuclear Argonaute HRDE-1 and may reflect stalling of RNA polymerase II and/or pre-mRNA processing, causing nascent transcripts to accumulate at the locus. Stalling of RNA polymerase has previously been implicated in nuclear RNAi 36,37 and several lines of evidence have linked RNAi and splicing, including apparent co-evolution of the RNAi and splicing machineries 38 , splicing factors identified as HRDE-1 interactors 39,40 , sRNA defects associated with mutations or knock down of spliceosome components 41,42 and insensitivity to nuclear RNAi of an endogenous transcript whose introns were removed by genome editing 43 .…”
Section: Pathway Ii: Hrde-1 Reduces But Does Not Eliminate Transcriptionmentioning
confidence: 99%
“…Strains expressing degron-GFP-integrated RPOA-2, RRB-1 or TSR-2 are homozygous viable and phenotypically wild-type with nucleolar RPOA-2 [37], nucle(ol)ar RRB-1 and nuclear TSR-2 localization patterns ( Figure-1B, Figure-S2A ), demonstrating that the degron-GFP tags are compatible with organism growth. To test the AID system, we then crossed strains expressing degron-GFP-integrated ribosome biogenesis factors (RPOA-2, RRB-1, TSR-2) with strains ubiquitously expressing TIR1 from the eft-3 promoter.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, after knocking down these genes by RNAi, a class of antisense ribosomal siRNAs (risiRNAs) were enriched, suggesting that the proper nucleolar localization of exosomes may be important for the suppression of risiRNA production. In addition, we also found that environmental stimuli, such as low temperature, induced the accumulation of risiRNAs that subsequently guide the nuclear Argonaute proteins NRDE-3 and NRDE-2 to the nucleoli, which are associated with pre-rRNAs and silence RNA polymerase I transcription (ZHOU et al 2017;LIAO et al 2021). Whether and how environmental stimuli could induce the translocation of exosome proteins in distinct subcellular compartments is intriguing.…”
Section: Introductionmentioning
confidence: 89%
“…In C. elegans, EXOS-10 and DIS-3 are ubiquitously expressed in all of the cells and enriched in the nucleus. Interestingly, EXOS-10 is enriched in nucleoli, while DIS-3 is enriched in the nucleoplasm but depleted in nucleoli (LIAO et al 2021). The RNA exosome functions both in the nucleus and cytoplasm to process noncoding RNAs (ncRNAs) and degrade improperly processed (faulty) RNAs in RNA surveillance pathways (HOUSELEY et al 2006;BUTLER AND MITCHELL 2010;SCHAEFFER et al 2010;SCHNEIDER AND TOLLERVEY 2013;KILCHERT et al 2016).…”
Section: Introductionmentioning
confidence: 99%